A Member of the Nuclear Receptor Superfamily, Designated as NR2F2, Supports the Self-Renewal Capacity and Pluripotency of Human Bone Marrow-Derived Mesenchymal Stem Cells - Ni Zhu; Huafang Wang; Binsheng Wang; Jieping Wei; Wei Shan; Jingjing Feng; He Huang (Stem Cells International)
Mesenchymal stem cells are characterized with self-renewal capacity and pluripotency. NR2F2 is a nuclear receptor that has been detected in the mesenchymal compartment of developing organs. However, whether NR2F2 plays a role in the stemness maintenance of mesenchymal stem cells has not been explored yet. In this study, we investigated the function of NR2F2 in bone marrow-derived mesenchymal stem cells via shRNA-mediated knock-down of NR2F2. The suppression of NR2F2 impaired the colony-forming efficacy of mesenchymal stem cells. The inhibition of colony-forming capacity may be attributed to the acceleration of senescence through upregulation of P21 and P16. The downregulation of NR2F2 also suppressed both osteogenic and adipogenic differentiation processes. In conclusion, NR2F2 plays an important role in the stemness maintenance of bone marrow-derived mesenchymal stem cells.